About habitats : mountains - Sill, Cathryn P., 1953-; Sill, John (Atlanta, Ga. : Peachtree, 2009)
Colorful illustrations and simple text introduce young readers to the different types of mountainous terrain and the various species of plant and wildlife that inhabit them.
Includes bibliographical references.
3.5
K-3
Keywords: Mountains -- Juvenile literature; Mountains; Mountains